If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -5(7m + 5) = 86 Reorder the terms: 6 + -5(5 + 7m) = 86 6 + (5 * -5 + 7m * -5) = 86 6 + (-25 + -35m) = 86 Combine like terms: 6 + -25 = -19 -19 + -35m = 86 Solving -19 + -35m = 86 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -35m = 86 + 19 Combine like terms: -19 + 19 = 0 0 + -35m = 86 + 19 -35m = 86 + 19 Combine like terms: 86 + 19 = 105 -35m = 105 Divide each side by '-35'. m = -3 Simplifying m = -3
| 2x+3+x=x+3 | | 18q^2-39qt-189t^2=0 | | 6x-1x=6-6 | | 2i/3i | | 2w+2(1w+283)=19 | | 5p-95p+119p-p=151 | | 3[x+5]=27 | | 8x^2+10x+25= | | 2(3a+1)=5(a-1) | | 66-2r+1=3r-5(r-2) | | F(10.5)= | | 28+x=14 | | 6=x-3/2 | | 2(p+5)-3(p-7)=43 | | (9x^7)(-8x^5)=0 | | 10(d+9)=210 | | 7x-7-5x=2 | | 40-[3c+4]=4[c+5]+c | | 40-[3c+4]=[c+5]+c | | 4m-3=6m+5 | | -7t+4=-10t-14 | | 4[m+4]=40 | | -7+4=-10+-14 | | 2x+50=110 | | 14x^4+92x-42x^2=0 | | 2x-3y+i(x-2y)=4-5i | | -4(7-5m+n)= | | 6+4b=2+5b | | -3=21m | | M+2M-2=0 | | 6(w+1)-(3-2w)=7w | | 3x2squared/12x6squared |